Factor H binding protein (FHbp): An evaluation of genotypic diversity across Neisseria meningitidis serogroups - Zhenghui Li; Ashlesh Krishna Murthy; Li Hao; Lubomira Andrew; Annaliesa S. Anderson (Human Vaccines & Immunotherapeutics)
Neisseria meningitidis serogroups A, B, C, W, X, and Y cause invasive meningococcal disease (IMD) worldwide. Factor H binding protein (FHbp), a key meningococcal virulence factor, is an antigen included in both licensed meningococcal serogroup B (MenB) vaccines. This review examines the biology and epidemiology of FHbp and assesses the ability and potential of FHbp vaccine antigens to protect against IMD. Using evidence from the literature and the contemporary PubMLST database, we discuss analyses of MenB genotypes on the representation of the most prevalent multilocus sequence typing (MLST)/clonal complexes, FHbp subfamily distribution, and FHbp and porin A (PorA) variants. We further discuss that the similar genotypes, distribution, and diversity of FHbp variant types have remained stable over long time periods, supporting the potential for FHbp-containing, protein-based vaccines to protect against IMD, including MenB-FHbp (Trumenba®), which contains two lipidated FHbp antigens (one each from both FHbp subfamilies: A and B).